Leitura juvenil sob a luz da leitura subjetiva: uma proposta para os anos finais do ensino fundamental - Gonçalves, Marlene Eurípedes (2023)
The formation of literary readers is one of the great challenges encountered in teaching Literature in the 21st century. This problem goes beyond elementary school and permeates high school, given the problem of conceiving literature as a pretext for teaching grammar or considering only its historiographical bias. This research, in view of the concern to offer a teaching of literature, in public schools, capable of forming critical and creative readers, aimed to carry out a bibliographical research on the formation of literary readers and youth literature through perspective of subjective reading; and in the assumptions of action research. For that, we use as theoretical support Rildo Cosson (2006-2013-2020), Barthes (1987), Antônio Cândido (1995), Chambers (2007), Cecília Bajour (2012), Colomer (2003-2008), Petit (2008), Rezende (2013), Langlade (2013), Jouve (2002 and 2013), Rouxel (2012 and 2013), and Thiollent (2008). The methodology used had the participation of a researcher and students of the 9th grade of Elementary School II, using reading/listening in a shared and autonomous way, of readers' reports in reading diaries, conversation circles and written production. The product consists of creative rewriting from the reading of the novel Senhor das Moscas, by William Golding, which resulted in the creation of new interpretations of the text. This research contemplated literary reading in the formation of young literary readers based on the conception of the reader's subjectivity.